Use of antithrombotic therapy in the management of factor XI deficiency: is it safe? Uso de terapia antitrombótica en el manejo de la deficiencia del factor XI: ¿es segura? - Hernández-Vides , Karen Margarita (2025)
Factor XI (FXI) deficiency represents a paradigm of unpredictable bleeding risk. However, emerging population-based evidence and accumulated clinical series consistently indicate that antithrombotic therapy can be administered with an acceptable safety profile. Clinical practice should rely on individualized risk stratification and the judicious selection of therapeutic agents, accompanied by regular clinical and laboratory monitoring. A shortage of prospective studies remains—particularly those including severe cases, comparing different anticoagulants, and assessing patient-centered outcomes. The naturally observed phenomenon supports the development of drugs targeting FXI/FXIa as a promising pathway toward anticoagulation with reduced bleeding risk. The most recent evidence invites the hematology and cardiovascular communities to transform a molecular “rarity” into an opportunity to rethink hemostasis and, perhaps, redefine the standard of antithrombotic therapy in selected populations.